Preparation and investigation of a novel combination of Solanum nigrum-loaded, arabinoxylan-cross-linked β-cyclodextrin nanosponges for the treatment of cancer: in vitro, in vivo, and in silico evaluation - Shah, Hamid Saeed; Zaib, Sumera; Khan, Imtiaz; Sliem, Mahmoud A.; Alharbi, Osama; Al-Ghorbani, Mohammed; Jawad, Zobia; Shahzadi, Kiran; Awan, Sajjad (Frontiers in Pharmacology, 2023)
Introduction: Cancer contributes to a high mortality rate worldwide spanning its diversity from genetics to resistant therapeutic response. To date emerging strategies to combat and manage cancer are particularly focused on the development of targeted therapies as conventional treatments account for the destruction of normal cells as well. In this regard, medicinal plant-based therapies are quite promising in imposing minimal side effects; however, limitations like poor bioavailability and stability of bioactive phytochemicals are associated with them. In parallel, nanotechnology provides nominal solution to deliver particular therapeutic agent without compromising its stability. Methods: In this study, Solanum nigrum, an effective medicinal plant, loaded arabinoxylan cross-linked β-cyclodextrin nanosponges (SN-AXCDNS) were designed to evaluate antitumor activity against breast cancer. Therefore, SN-AXCDNS were prepared by using cross-linker melt method and characterized by physicochemical and pharmacological parameters. Results: Hydrodynamic size, zeta potential and entrapment efficiency (EE%) were estimated as 226 ± 4 nm, −29.15 ± 5.71 mV and 93%, respectively. Surface morphology of nanocomposites showed spherical, smooth, and porous form. Antitumor pharmacological characterization showed that SN loaded nanosponge demonstrated higher cytotoxicity (22.67 ± 6.11 μg/mL), by inducing DNA damage as compared to void SN extract. Flow cytometry analysis reported that encapsulated extract promoted cell cycle arrest at sub-G1 (9.51%). Moreover, in vivo analysis demonstrates the reduction in tumor weight and 85% survival chances in nanosponge treated mice featuring its effectiveness. In addition, in silico analysis revealed that β-cyclodextrin potentially inhibits MELK in breast cancer cell lines (B.E = −10.1 Kcal/mol). Conclusion: Therefore, findings of current study elucidated the therapeutic potential of β-cyclodextrin based nanosponges to be an alternative approach regarding the delivery and solubilization of antitumor drugs.